Metabolic turnover of cysteine-related thiol compounds at environmentally relevant concentrations by Geobacter sulfurreducens - Gutensohn, Mareike; Schaefer, Jeffra K.; Maas, Torben J.; Skyllberg, Ulf; Björn, Erik (Frontiers in Microbiology, 2023)
Low-molecular-mass (LMM) thiol compounds are known to be important for many biological processes in various organisms but LMM thiols are understudied in anaerobic bacteria. In this work, we examined the production and turnover of nanomolar concentrations of LMM thiols with a chemical structure related to cysteine by the model iron-reducing bacterium Geobacter sulfurreducens. Our results show that G. sulfurreducens tightly controls the production, excretion and intracellular concentration of thiols depending on cellular growth state and external conditions. The production and cellular export of endogenous cysteine was coupled to the extracellular supply of Fe(II), suggesting that cysteine excretion may play a role in iron acquisition and/or cellular trafficking to iron proteins. Addition of excess exogenous cysteine resulted in a rapid and extensive conversion of cysteine to penicillamine by the cells. Experiments with added isotopically labeled cysteine confirmed that penicillamine was formed by a dimethylation of the C-3 atom of cysteine and not via indirect metabolic responses to cysteine exposure. This is the first report of de novo metabolic synthesis of this compound. Penicillamine formation increased with external exposure to cysteine but the compound did not accumulate intracellularly, which may suggest that it is part of G. sulfurreducens‘ metabolic strategy to maintain cysteine homeostasis. Our findings highlight and expand on processes mediating homeostasis of cysteine-like LMM thiols in strict anaerobic bacteria. The formation of penicillamine is particularly noteworthy and this compound warrants more attention in microbial metabolism studies.